2007
DOI: 10.1210/en.2006-1022
|View full text |Cite
|
Sign up to set email alerts
|

Glucotoxicity Inhibits Late Steps of Insulin Exocytosis

Abstract: Prolonged exposure of beta-cells to high glucose (glucotoxicity) diminishes insulin secretion in response to glucose and has been linked to altered generation of metabolism-secretion coupling factors. We have investigated whether glucotoxicity may also alter calcium handling and late steps in secretion such as exocytosis. Clonal INS-1E beta-cells cultured at high glucose (20 or 30 mM vs. 5.5 mM) for 72 h exhibited elevated basal intracellular calcium ([Ca2+]i), which was KATP-channel dependent and due to long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 56 publications
6
67
1
2
Order By: Relevance
“…4). In the case of vesicle-associated membrane protein (VAMP)-2, synaptotagmin-like protein 4 (Sytl4), and Rab3b, who interact upon Ca 2ϩ increase, this has been observed before (26,27 expression of Sytl4 reduces the number of docked vesicles to the plasma membrane, which is suggested to effect insulin secretion (19,28). Decreased mRNA and protein expression of VAMP2 and various other secretory proteins have also been associated with impaired protein secretion in diabetic patients (29) and animal models for diabetes (30).…”
Section: Resultsmentioning
confidence: 87%
“…4). In the case of vesicle-associated membrane protein (VAMP)-2, synaptotagmin-like protein 4 (Sytl4), and Rab3b, who interact upon Ca 2ϩ increase, this has been observed before (26,27 expression of Sytl4 reduces the number of docked vesicles to the plasma membrane, which is suggested to effect insulin secretion (19,28). Decreased mRNA and protein expression of VAMP2 and various other secretory proteins have also been associated with impaired protein secretion in diabetic patients (29) and animal models for diabetes (30).…”
Section: Resultsmentioning
confidence: 87%
“…[16][17][18][19][20][21][22] Basal insulin release at 5.6 mM glucose was not affected by hyperglycemia but the secretory response to 16.7 mM glucose was impaired by 48 and 72 h exposure to 25 mM glucose. We also observed that insulin release from 1.1B4 cells chronically exposed to hyperglycemia for 48 and 72 h was significantly reduced in response to alanine, GLP-1, KCl, elevated Ca 2+ , or forskolin.…”
Section: Discussionmentioning
confidence: 98%
“…Plasmids encoding ADCY8, ADCY8-eGFP and myc-GLP1R were generously donated by D. Cooper (University of Cambridge, UK) and A. Bisello (University of Pittsburgh, PA, USA). Plasmids encoding control short hairpin RNA (shRNA) or shRNA directed against ADCY8 were from SABiosciences (Frederick, MD, USA), the plasmid encoding human growth hormone (hGH) has been described [16,17]. CD8-eGFP was obtained by replacing the cytosolic domain of CD8 with eGFP.…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged exposure to elevated levels of glucose alters calcium handling in a cAMP-dependent manner [15,16]. As the incretin GLP-1 exerts most of its effects through these second messengers and its efficacy is partially lost in type 2 diabetes, we used this hormone to investigate the interplay between cAMP and calcium under exposure to normal and chronically elevated glucose levels to identify underlying changes in signal transduction and gene expression.…”
Section: Introductionmentioning
confidence: 99%